Satisfacción laboral de las enfermeras en salas de hospitalización de adultos. Un sentimiento ambivalente (2012)
ABSTRACT: To know and understand job satisfaction of nursing professionals in adult hospitalization wards in institutions of the Metropolitan Area of Valle de Aburrá (Colombia). Methodology. This was a qualitative study, frame-worked within the ethnographic paradigm. During 2008, semi-structured interviews were made to 15 female nursing professionals and two male nursing professionals, in addition to 30 hours of observation in their work places, with prior signed consent and authorization from the institutions. Results. The following categories emerged: satisfaction, dissatisfaction, and ambivalence between job satisfaction and dissatisfaction of the nursing professionals; with dissatisfaction being the primordial feeling among them. Nursing professionals feel satisfaction when patients leave recovered, when they provide direct care, or when there are positive results through their work. Dissatisfaction appears when they cannot provide direct care, lose autonomy, are overloaded with work, or because job demand diminishes. Conclusion. Job satisfaction is an ambivalent feeling, dissatisfaction prevailing in the study group.